Can invariant Natural Killer T cells drive B cell fate? a look at the humoral response - Palacios, Pablo A.; Santibañez, Álvaro; Aguirre-Muñoz, Fernanda; Gutiérrez-Vera, Cristián; Niño de Zepeda-Carrizo, Valentina; Góngora-Pimentel, Martín; Müller, Marioly; Cáceres, Mónica; Kalergis, Alexis M.; Carreño, Leandro J. (Frontiers in Immunology, 2025)
Invariant Natural Killer T (NKT) cells represent a unique subset of innate-like T cells that express both NK cell and T cell receptors. These cells are rapidly activated by glycolipid antigens presented via CD1d molecules on antigen-presenting cells (APCs), including B cells, dendritic cells (DCs), and macrophages, or through cytokine-dependent mechanisms. Their ability to produce a wide range of cytokines and express costimulatory molecules underscores their critical role in bridging innate and adaptive immunity. B cells, traditionally recognized for their role in antibody production, also act as potent APCs due to their high expression of CD1d, enabling direct interactions with iNKT cells. This interaction has significant implications for humoral immunity, influencing B cell activation, class-switch recombination (CSR), germinal center formation, and memory B cell differentiation, thus expanding the conventional paradigm of T cell–B cell interactions. While the influence of iNKT cells on B cell biology and humoral responses is well-supported, many aspects of their interaction remain unresolved. Key questions include the roles of different iNKT cell subsets, the diversity of APCs, the spatiotemporal dynamics of these interactions, especially during early activation, and the potential for distinct glycolipid ligands to modulate immune outcomes. Understanding these factors could provide valuable insights into how iNKT cells regulate B cell-mediated immunity and offer opportunities to harness these interactions in immunotherapeutic applications, such as vaccine development. In this review, we examine these unresolved aspects and propose a novel perspective on the regulatory potential of iNKT cells in humoral immunity, emphasizing their promise as a target for innovative vaccine strategies.